Developing an instrument to measure Malaysian highland farmers' adaptation towards climate change - Idris, Khairuddin; Abu Samah, Asnarulkhadi; Abu Samah, Bahaman; Sahharon, Hamizah; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2017)
This paper aims to explicate the instrument development process for measuring Malaysian highland farmers’ adaptation towards climate change. The process consisted five phases, namely understanding the background of study, comprehensive review of literature; detailed review of each item; establishing the reliability of instrument and strengthening the instrument. Based on the reliability analysis and validity procedures by the research team, several modifications were made. The finalized instrument contains a total of five sections, namely demographic (18 items), cognitive (12 items), practices (seven items), structure (nine items) and cost (15 items). Towards the end, the researchers planned to use the developed instrument to conduct a related study at three main highland farming areas in Malaysia namely Lojing, Cameron Highland and Kundasang.